Career Readiness and Resilience as Predictors of Entrepreneurial Intention: The Mediating Role of Entrepreneurial Self-Efficacy among University Students - Lalu Agustino; Muhammad Nawawi; Muhammad Ridhoni (International Journal of Business and Quality Research, 2025)
Entrepreneurial intention (EI) among university students has become an increasingly important topic in entrepreneurship studies, particularly in developing economies where youth unemployment poses major challenges. Although earlier works have acknowledged the roles of career readiness and resilience in shaping EI, the mediating influence of entrepreneurial self-efficacy (ESE) has received less systematic attention. This study investigates how career readiness and resilience contribute to EI, with ESE positioned as a mediating construct.Survey data were obtained from 200 undergraduate students in Indonesia who were not enrolled in business programs. The dataset was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Measurement model assessment indicated strong reliability and convergent validity, while discriminant validity was confirmed using the Fornell–Larcker criterion and HTMT ratios. Structural model results revealed that career readiness exerts a significant effect on EI (β = 0.633, p < 0.001), both directly and indirectly through ESE. Likewise, resilience significantly predicted EI (β = 0.123, p < 0.01) and had a strong effect on ESE (β = 0.521, p < 0.001), which subsequently enhanced EI (β = 0.411, p < 0.001). Altogether, the model accounted for 82.3% of the variance in EI, demonstrating high explanatory power.The findings emphasize the crucial mediating role of ESE as a psychological channel through which career readiness and resilience translate into entrepreneurial motivation. This study adds to entrepreneurship research by linking psychological capital and career preparedness to entrepreneurial intention. From a practical standpoint, universities are encouraged to develop programs that foster resilience, strengthen career readiness, and build entrepreneurial self-efficacy, thereby equipping students not only to enter the labor market but also to create employment opportunities.